Specific rights and needs for protection of the victims of crime in relation to their participation in criminal proceedings - Nedyalkova, Elena (Law Journal of New Bulgarian University, 2023)
The article explores procedural remedies and measures for protecting the rights and legitimate interests of victims of crimes based on Bulgarian and international legislation. The possibility of issuing an European protection order has been also analyzed.